A qualitative study examining UK female genital mutilation health campaigns from the perspective of affected communities. (October 2020) - Salmon, D.; Olander, E.K.; Abzhaparova, A.
Abstract: Objectives: Female genital mutilation (FGM) is a worldwide problem associated with severe health risks. In the UK, preventative public health campaigns have been developed to eradicate FGM. The aim of the present study was to elicit the views about FGM public health campaigns from the perspective of a UK Somali community. Study design: Three focus groups and one interview were conducted with 16 community members. Methods: Using posters and leaflets focused on UK FGM prevention, photo-elicitation was used to encourage participants to discuss the usefulness and implications for national public health messages aimed at eradicating FGM. Data were subjected to inductive thematic analysis. Results: Participants were positive about the aims of the campaigns presented within the research, believing such campaigns were necessary and increased awareness of FGM. However, participants felt the campaigns also carried risks of enhancing stereotypes in terms of ethnicity, gender and religion. For example, some images were perceived to suggest that FGM was only relevant to Sub-Saharan women, although it is also prevalent in other populations. Some fathers reported feeling unfairly targeted in campaigns that focused on the role of mothers in protecting daughters from FGM. Participants were also concerned that some poster images may suggest that FGM was associated with Islam and perceived as a religious issue, rather than a cultural one. Fears were identified that this could lead to stigmatisation and hostility towards those affected. Conclusions: The research findings suggested that actively working with affected communities to develop messaging that counters negative stereotyping and associated hostility should be a priority. Highlights: Public health campaigns often focus on eradicating FGM using a range of messages for targeted audiences. From the perspective of affected communities, campaigns are seen as necessary and important in raising awareness. Some campaigns could enhance stereotypes in terms of ethnicity, gender and religion. Working with affected communities to produce appropriate messaging within campaigns is needed to maximise their effectiveness and prevent stigma and hostility towards those affected.